THE EFFECT OF A PLANT-DERIVED ANTIOXIDANT ON THE CORRECTION OF GINGIVAL DYSTROPHIC-INFLAMMATORY CHANGES IN PUBERTAL RATS - Romanenko, Ye.G.; Еismund, P.A.; Khotimska, Yu.V.; Lavreniuk, Ya.V.; Holub, A.V.; Samoilenko, I.I.; Dudko, А.S. (World of Medicine and Biology, 2025)
Impaired barrier properties of the gingival epithelium play a principal role in the pathogenesis of periodontal diseases in adolescents, especially secondary to diseases of the upper gastrointestinal tract. Microcirculatory disorders activate processes of free radical oxidation with subsequent structural disorganization of gingival tissues. The purpose of the study was to examine the effect of a plant-derived antioxidant on the correction of dystrophic-inflammatory changes in the gingival tissues in pubertal rats with simulated reflux gastritis by analyzing morphological alterations. The model of hyposecretory reflux gastritis was induced by intragastric administration of medical bile to 23 pubertal Wistar rats of both sexes once a day for 15 days. The animals received an herbal preparation with an antioxidant effect and placebo therapy for the next 15 days. Gingival specimens were processed for histological analysis and visualized using a microscopic method after animal sacrifice. Morphological alterations in the gingival tissues of rats with induced reflux gastritis represented phenomena characteristic of vascular and stromal protein dystrophies with an inflammatory component as a sign of dystrophic-inflammatory processes. The use of the plant-derived antioxidant stimulated processes of epithelial proliferation and promoted cell differentiation amid the recovery of microcirculation.
Keywords: gingiva; hypoxia; free radical oxidation; dystrophy; reflux; gastritis; antioxidant therapy